2015
DOI: 10.1186/s40711-015-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

From capital to habitus: class differentiation of family educational patterns in urban China

Abstract: Based on Bourdieu's concepts of "capital" and "habitus" in his class theory, this paper examines the differentiation of capital investment and parenting habitus on children's education between the Chinese urban middle class and lower class. By analyzing 2009 survey data of students in grades 4 and 8 in urban areas, the authors found that middle-class parents had significant advantages in capital investment, but showed no significant differences in parenting attitudes when compared to lower-class families. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 21 publications
0
33
1
Order By: Relevance
“…The field is the basis for the existence of habituation, and habituation is the meaning of the existence of the field. Capital determines the formation of habitus, and habitus is the reflection of capital condition and the condition of obtaining capital [7]. In the current rural field, the habitus structure of individual farmers exists in the form of division of labor between men and women, material world, consumption mode, kinship relationship and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field is the basis for the existence of habituation, and habituation is the meaning of the existence of the field. Capital determines the formation of habitus, and habitus is the reflection of capital condition and the condition of obtaining capital [7]. In the current rural field, the habitus structure of individual farmers exists in the form of division of labor between men and women, material world, consumption mode, kinship relationship and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The value of capital depends on the existence of the field in which it works. Each field is a place of struggle [7].…”
Section: Tools Of Social Practice: Rural Capitalmentioning
confidence: 99%
“…Prior research indicated that rural and urban parents showed disparate ways educating children. Rural adolescents were closer to their mothers than their urban counterparts; urban adolescents reported more con icts with their parents than their rural ones [36]. Considering the rural and urban differences, this research proposed the following two hypotheses: H1: Urban and rural parents had different feeding knowledge and practices in China;…”
Section: Parental Monitoring and Restricting Behaviors And Children Amentioning
confidence: 94%
“…Prior research indicated that rural and urban parents showed disparate ways educating children. Rural adolescents were closer to their mothers than their urban counterparts; urban adolescents reported more con icts with their parents than their rural ones [36]. Considering the rural and urban differences, this research proposed the following two hypotheses: H1 Urban and rural parents had different feeding knowledge and practices in China H2 Urban and rural parents' feeding knowledge and practices impacted Chinese children and adolescents' weight status in different manners.…”
Section: Parental Monitoring and Restricting Behaviors And Children Amentioning
confidence: 94%